USING MOLECULAR ELECTROSTATIC POTENTIALS AND FRONTIER ORBITALS FOR THE SURFACE-ENHANCED RAMAN INTERPRETATION OF FLUOXETINE - Díaz Fleming, Guillermo; Martínez Ortiz, Úrsula; Zapata León, Freddy; Koch, Rainer (Journal of the Chilean Chemical Society, 2019)
Raman and surface-enhanced Raman (SERS) spectra of (N-methyl-3-phenyl-3-[4-(trifluoromethyl)phenoxy)propane-1-amine hydrochloride, fluoxetine, have been recorded. Density functional theory with the B3LYP functional was used for optimization of the ground state geometry, calculation of the Raman normal modes of this molecule and the modelling of the SERS effect. Calculated geometrical parameters of fluoxetine fit well with the experimental ones. Based on the recorded data, the DFT results and a normal coordinate analysis based on a scaled quantum mechanical (SQM) force field approach, a complete vibrational assignment of fluoxetine as well as its adsorption behavior on a silver surface (using SERS selection rules) is derived.